دور التعليم العالي عن البعد في تحقيق الحراك المهني للطلبة غير المتفرغين - ببه, بدر الدين; حمزاوي, سهى (جامعة الوادي - University of Eloued, 2023)
تهدف دراستنا إلى بحث إشكالية دور التعليم العالي عن بعد في تحقيق الحراك المهني للطلبة غير المتفرغين من وجهة نظر طلبة جامعة البليدة 2 من خلال دراسة ميدانية لعينة منهم، أين تم اعتماد المنهج الوصفي في تحليل الموضوع ومناقشة الفرضيات بناءا على استجابات المبحوثين والتي بلغت 19.12%، فيما خلصت النتائج إلى وجود دور نسبي وليس مطلق للتعليم العالي عن بعد في الحراك المهني لدى أغلبية المبحوثين، في حين يرى البعض بأن الطلب على التخصص المدروس في سوق العمل ومدى انسجامه مع طبيعة نشاط التنظيم من أهم عوامل الحراك المهني. Our study aims to investigate the problem of the role of distance higher education in achieving the professional mobility responsible students from the point of view of Blida University students through a field study of a sample of them, where the descriptive approach was adopted in analyzing the subject and discussing hypotheses of this students, which amounted to 19.12%, While the results concluded that there is a relative and not an absolute role for distance higher education in the professional mobility of the majority of the respondents, while some believe that The compatibility of the studied demand in the market with the nature of the regulatory activity are one of the most important factors in the professional mobility.
دراسة حالة مجموعة من طلبة جامعة البليدة 2
مقال
Keywords: التعليم العالي عن بعد ; الحراك المهني ; الطالب غير المتفرغ; Distance higher education; professional mobility; part-time student